The Dialysis Outcomes and Practice Patterns Study (DOPPS) in Turkey. Issue 3 (25th October 2016) - Ecder, Tevfik; Utas, Cengiz; Ates, Kenan; Bieber, Brian; Robinson, Bruce M.; Pisoni, Ronald L.; Süleymanlar, Gültekin
Abstract: Introduction: Turkey has one of the largest treated end‐stage renal disease (ESRD) patient populations in Europe (N = 66, 711). In 2013, the international Dialysis Outcomes and Practice Patterns Study (DOPPS), a prospective study of hemodialysis (HD) practices and outcomes, initiated data collection in Turkey. Here we provide comparisons of HD patients in DOPPS‐Turkey with other international regions and with patients in the Registry of Turkish Nephrology, Dialysis and Transplantation. Methods: DOPPS‐Turkey study sites were randomly selected from all Turkish HD units treating ≥25 in‐center chronic HD patients. Detailed patient‐ and facility‐level data were collected for 20–30 randomly selected prevalent HD patients per facility. Findings: Demographic and comorbidity profiles for DOPPS‐Turkey patients were similar to HD patients overall in the 2013 Turkish Registry Report. In Turkey: diabetes was the most common ESRD cause (37%); arteriovenous fistula use was 83%; mean single pool Kt/V was 1.61. Compared with other international regions, Turkey had the highest mean hemoglobin (11.5 g/dL), ferritin (771 ng/mL), and interdialytic weight gain (3.28%), while Turkey had the lowest mean systolic blood pressure (127 mmHg) and erythropoiesis stimulating agent prescription (57%). Turkish patients also reported the highest depression scores. Discussion: In this first DOPPS‐Turkey report, the DOPPS sample agrees well with national Turkish Registry data. Treatment and laboratory data, and patient‐reported outcomes, demonstrate similarities and previously unrecognized contrasts to DOPPS findings in Europe, Japan, and North America. Long‐term follow‐up of these patients will describe how these differences relate to clinical outcomes within Turkey.